Borders, Boundaries, and Exclusion in the Icelandic Asylum System - Tryggvadóttir, Helga Katrín; Skaptadóttir, Unnur Dís (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2018)
Grounded in theories of borders and boundaries, this article critically engages with the processes through which asylum seekers in Iceland are excluded from full participation in society. Immigration laws and bureaucratic barriers contribute to this exclusion, which is a result of restrictions on labour market participation, lack of housing, temporality, and lack of meaningful activities. We discuss how borders and boundaries create the identity of the asylum seeker and how the participants in this study experience that identity. We identify three main areas of exclusion: social exclusion, isolation, and cultural boundaries.